1981
DOI: 10.1302/0301-620x.63b3.7021561
|View full text |Cite
|
Sign up to set email alerts
|

Management of deep infection of total hip replacement

Abstract: Exchange operation is recommended as the treatment of choice for most deep infections involving a total hip replacement. This revision arthroplasty comprises, in one stage, excision of soft tissue, removal of implant and cement, replacement with an appropriate implant using Palacos R acrylic cement loaded with an appropriate antibiotic and, more recently, systemic antibiotics. During our first 10 years without systemic antibiotics we have achieved an overall 77 per cent success rate from a first attempt in 583… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
263
0
25

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 632 publications
(291 citation statements)
references
References 0 publications
3
263
0
25
Order By: Relevance
“…__________________________ This is the authors' final version prior to publication in The Journal of Arthroplasty 22(6, Suppl. [5] 7/19 (37%) Revision hip and knee Athanasou et al [6] 3/84 (4%) Revision hip and knee Padgett et al [7] 43/142 (30%) Revision hip Barrack and Harris [8] 54/260 (21%) Revision hip Lachlewicz et al [9] 2/21 (10%) Revision hip Duff et al [10] 1/19 (6%) Revision knee Mirra et al [11] 5/27 (19%) Revision hip and knee Kamme and Lindberg [12] 10/31 (32%) Primary hip Kamme and Lindberg [12] 13/25 (52%) Revision hip Bucholz et al [13] 80/667 (12%) Revision hip Spangehl et al [1] 6/180 (3%) Revision hip …”
Section: Resultsmentioning
confidence: 99%
“…__________________________ This is the authors' final version prior to publication in The Journal of Arthroplasty 22(6, Suppl. [5] 7/19 (37%) Revision hip and knee Athanasou et al [6] 3/84 (4%) Revision hip and knee Padgett et al [7] 43/142 (30%) Revision hip Barrack and Harris [8] 54/260 (21%) Revision hip Lachlewicz et al [9] 2/21 (10%) Revision hip Duff et al [10] 1/19 (6%) Revision knee Mirra et al [11] 5/27 (19%) Revision hip and knee Kamme and Lindberg [12] 10/31 (32%) Primary hip Kamme and Lindberg [12] 13/25 (52%) Revision hip Bucholz et al [13] 80/667 (12%) Revision hip Spangehl et al [1] 6/180 (3%) Revision hip …”
Section: Resultsmentioning
confidence: 99%
“…However, the specificity is generally lower, especially when patients with rheumatoid arthritis are included [20,25,65], and it does not identify the microorganism in question. Aspiration and biopsy offer the only chance of identifying the infective microorganism preoperatively [9,23,49,50]. Identifying the causative pathogen and its sensitivity can alter antibiotics given at the time of a revision arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings suggest the ability to control infection is improved with the addition of antibiotic-laden bone cement, the series with the largest patient cohort, consisting of 583 patients published by Buchholz et al, had findings more similar to our own series. Specifically, the authors reported a success rate defined as no recurrent infection, loosening, and useful function of 77% (448 of 583) after an initial one-stage exchange arthroplasty, which improved to 88% (510 of 583) after a subsequent one-stage procedure [10].…”
Section: Discussionmentioning
confidence: 99%
“…One-stage exchange arthroplasty was originally described by Buchholz et al [10] in the 1970s and is still widely used in several centers, particularly in Europe. The ability of the procedure to control infection is believed to rely on strict surgical indications, preoperative identification of the infecting organism, aggressive surgical débridement, and implantation of components with antibiotic-laden bone cement [11,30,32].…”
Section: Introductionmentioning
confidence: 99%